"Do you talk normal?": Piecing together learning experiences with emergent bilingual preschoolers. (June 2022) - Miller Marsh, Monica; Mariyam, Mustary; Durant, Kathleen; Zhulamanova, Ilfa
Preschool teachers have a responsibility to create a sense of belonging for all children and families in their classroom community. Utilizing a funds of identity approach, this study examines how one preschool teacher uncovered the resources emergent bilingual children brought with them from home into school. She used this knowledge to intentionally create a play-based curriculum that strengthened relationships between and among children and provided spaces for the formation of positive social and educational identities. The participatory action research took place in a university laboratory school located in the Midwestern United States of America over a 2-year period. The study illuminates much about the lives of two emergent bilingual boys as they grow and learn in the quotidian space of the communal classroom environment.